The Invisible Threat: Investigating the Effects of Air Pollution on Human Health and the Environment - Fitria Hayu Palupi; Andi Tenri Abeng (West Science Interdisciplinary Studies, 2023)
The research study investigated the impact of air and environmental pollution on human health in Depok. A mixed-methods approach was employed, combining quantitative analysis of pollutant concentrations and health outcomes with qualitative insights from interviews. The findings revealed elevated levels of particulate matter (PM2.5) and nitrogen dioxide (NO2) in Depok, indicating poor air quality. Significant associations were observed between pollution exposure and respiratory symptoms, as well as cardiovascular diseases. The qualitative data emphasized the concerns and experiences of the residents, highlighting the need for awareness and protective measures. The study contributes to the understanding of the invisible threats posed by air and environmental pollution in Depok and calls for targeted interventions to mitigate the health risks.